The Impact of Stock Market Development and Credit Market Development on Technological Innovation: An Empirical Study Based on Cross-Country Panel Data - Chen, Tong; Nie, Changhong (Asian Economic and Financial Review, 2022)
Technological innovation is crucial to economic growth and social transformation. In the process of technological innovation, financial capital is indispensable. Accordingly, a country’s stock market and credit market are extremely important in giving impetus to technological innovation. Thus, we construct a panel data model with interactive fixed effects to study the impact of stock market development and credit market development on technological innovation in countries at different levels of economic development. Results indicate that, whether for developed or developing and emerging market countries, the development of the stock market has a significant positive influence on national technological innovation (NTI), and the impact of the development of the credit market on innovation of different types of countries is quite different. In addition, foreign direct investment (FDI) inflow can increase the positive impact of stock market development on NTI, but this impact is not significant for the sample of developed countries.